The role of state forest enterprises in the payments for forest environmental services programme in Vietnam - Milan, Florence M.; Huong, T.T.T.; Huong, Chu Thai; Suhardiman, Diana; Phuong, N.D.; Zeller, M. (2017)
To promote pro-poor payments for environmental services, it is necessary to identify institutional options that reduce transaction costs and organisational problems associated with establishing and maintaining contracts with small-scale environmental service providers. This study examined the dual functionality of state forest enterprises (SFEs) in the implementation of the Payments for Forest Environmental Services (PFES) Program in Vietnam. We considered whether SFEs’ involvement in the programme could reduce transaction costs and organisational problems. Data were collected from Tu Ly SFE in Hoa Binh province, northern Vietnam and from implementing agencies at various institutional levels. A survey of households participating in the SFE loan programme, and two stakeholder workshops were executed in 2014. The results revealed that Tu Ly SFE plays an important role in the livelihood of many farmers. A SWOT analysis exhibited SFEs’ advantage over other state agencies in implementing national forest management programmes as there are fewer parties involved with greater autonomy and outreach in the district. This study proposes the acknowledgment of SFEs as environmental service providers in their own forestlands and to use SFEs as intermediaries in the Payments for Forest Environmental Services Programme activities.